Revolutionizing Logistics Business Models through Big Data and Blockchain: A Business Model Canvas Analysis - Indah Ainun Mutiara; Yusuf Febriansyah; Mustofa Kamal; Ramzi Zainum Ikhsan; Tane Williams (Pandawan Sejahtera Indonesia, 2024)
The world is moving quickly towards automation and digitalization in the modern era. This change is becoming crucial to corporate competitive strategies, especially in the logistics industry. The use of data in organizational decision-making is an essential aspect of this digital and automated environment. Several business sectors are implementing Big Data and Blockchain technologies to improve organizational capabilities by developing effective business processes. This inexorably affects the development of new business models that fit the changing global business landscape. The Business Model Canvas (BMC) is an effective tool for analyzing internal and external business model changes. A SWOT analysis of these business model transformations is necessary to explain the new business process changes further. First, the analysis shows that for businesses to function at their best, current technological advancements—particularly in Big Data and Blockchain—will continue to disrupt them. Second, there have been significant internal and external changes to intra- and inter-organizational relationships due to the implementation of Big Data and Blockchain. Thirdly, the benefits of Blockchain and Big Data technologies for business, especially logistics, can be further explained by SWOT analysis.